Pengenalan dan Edukasi Deteksi Dini Penyakit Kulit di Daerah Pesisir Pantai Ampenan, Lombok NTB - Dinni Ramdhani K; Dedianto Hidajat; Niti Wedayani A.A.A (Universitas Mataram, 2022)
Background: Skin health problems are one of the most common diseases in coastal communities, caused by various factors, including personal hygiene, water conditions, and humidity. In the research that has been done, it is said that skin disease in coastal communities is a major problem for people living in coastal areas. Until now, skin diseases in coastal areas are still a problem for most Indonesian people, most of whom live on the coast. Situation Analysis: Health workers play an important role in disseminating knowledge about skin diseases that often appear in coastal communities, one of which is by organizing early detection counseling activities. Through this activity, it is hoped that there will be an increase in public knowledge about early detection of skin diseases that may appear in coastal communities. Method: The approach steps taken in this program consist of counseling the general public regarding the early detection of skin diseases in coastal communities. Results and Conclusions: In the provision of education which was preceded by a pre-test first, it showed that the people of the coastal area of Ampenan had low awareness and level of knowledge related to Skin Health, from 30 people who had been given education it was known that 25 people got a score of less than 50. After being given education about skin health and early detection of skin health, then an evaluation was carried out. It was found that there was an increase in the score to 20 people with a score above 50. Through these results, it is known that education on the introduction and early detection of skin diseases is important because it can prevent the severity and increase the number pain caused by skin diseases